The long-term mechanical performance of geogrid-reinforced soil retaining walls under cyclic footing loading. (December 2022) - Liu, Ying; Zhao, Yongzhe; Zhang, Deng; Liu, Zhiyong
Abstract: The soil behind the retaining wall may be subjected to various cyclic loadings, for example, machine vibration, traffic and earthquake loading. To reduce soil deformation and improve the stability of a soil retaining wall, geosynthetics have been widely used for wall reinforcement. A set of physical model tests were performed to investigate the long-term mechanical performance of geogrid-reinforced soil retaining walls under cyclic footing loading. Fujian standard sand was used as the backfill in all the tests. Different locations of the footing relative to the retaining wall and locations of geogrid failure were considered in the test series. The soil retaining wall lateral deflections, footing settlement, vertical soil stress and geogrid strain were presented and discussed. Digital image correlation (DIC) analysis was performed to reproduce the ground deformation under different testing conditions. The test results show that the footing settlement is attributed to the cyclic loading-induced soil deformation and the settlement caused by the lateral facing deflection of the wall. In addition, the lateral facing deflection of the wall reduces the lateral confinement in the soil, which increases the cyclic loading-induced footing settlement. However, the effect of the lateral facing deflection of the wall on the footing settlement becomes limited if the footing is 4B from the soil retaining wall. The failure of the geogrid leads to greater lateral facing deflection of the retaining wall and a deeper zone of influence of the cyclic loading, so greater footing settlement can be observed than that in the tests without geogrid failure. Larger lateral deflection is associated with smaller vertical soil stress accumulation. The geogrid strain accumulation is largest directly below the footing and is related to vertical soil stress accumulation.